The influence of Imipenem resistant metallo-beta-lactamase positive and negative Pseudomonas aeruginosa nosocomial infections on mortality and morbidity - Babu, Kolhal Veerappa Yogeesha (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Metallo-beta-lactamase (MBL) mediated resistance to carbapenems is an emerging threat in Pseudomonas aeruginosa (PA) nosocomial infections. Limited data on role of Imipenem resistant MBL positive PA (IR-MBLP-PA) and IR-MBL negative-PA (IR-MBLN-PA) infections on mortality and morbidity initiated the present study. OBJECTIVES: The aim of this study is to determine the role of IR-MBLP-PA and IR-MBLN-PA infections on mortality and morbidity. MATERIALS AND METHODS: Prospective observational study of 1 year with 110 PA nosocomial infections was conducted with Imipenem + ethylene-diamine-tetra-acetic acid combined disc test for MBL detection. Role of IR-MBLP-PA and IR-MBLN-PA infections on the outcome and morbidity were assessed in terms of crude mortality rate, Charlson's comorbidity score and mean duration of stay in intensive care unit (ICU) until cure and until death, number of episodes of complications and underlying disease. Results were analyzed by z test for proportions and Student t-test. RESULTS: Relatively high crude mortality was observed among IR-MBLP-PA infections than IR-MBLN-PA (42.86% [6/14] vs. 20% [2/10], Z = 0.69, P = 0.49 NS). Ventilator-associated pneumonia was the underlying disease and a confounding factor in all deaths due to IR-MBLP-PA infections. IR-MBLP-PA infections resulted in rapid downhill course to death with short mean duration of stay in ICU until death than IR-MBLN-PA infections (3.167 ± 0.98 days vs. 16 ± 2.82, P < 0.001 highly significant [HS]) with more number of complications (5.85 ± 1.65 vs. 3.7 ± 1.31, P < 0.001 HS). With the exception of previous Imipenem therapy, association of higher Charlson's comorbidity score, severe underlying diseases, multidrug and pandrug resistance and pre-disposing risk factors with IR-MBLP-PA infections was not statistically significant. CONCLUSIONS: Higher mortality in IR-MBLP-PA than in IR-MBLN-PA was not significant indicating IR as an important predictor of mortality than MBL production. Higher morbidity and increased virulence was observed with certainty in IR-MBLP-PA infections.